2018
DOI: 10.2215/cjn.12521117
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Benefits of Antimicrobial Stewardship Programs in Hemodialysis Facilities

Abstract: The model suggests that implementation of antimicrobial stewardship programs in outpatient dialysis facilities would result in substantial reductions in infections caused by multidrug-resistant organisms and , infection-related deaths, and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The predominance of Klebsiella pneumoniae and Pseudomonas species observed in our study cohort mirrored the high prevalence of Gram Negative Bacteria (GNB) reported in the Indian population, warranting the use of reserved drugs like polymyxins in healthcare settings across the country [ 4 , 20 ]. Our study emphasizes the importance and effectiveness of ASP initiatives in improving the indiscriminate prescription patterns of last resort antimicrobials used in the treatment of MDR organisms and potential survival benefits [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The predominance of Klebsiella pneumoniae and Pseudomonas species observed in our study cohort mirrored the high prevalence of Gram Negative Bacteria (GNB) reported in the Indian population, warranting the use of reserved drugs like polymyxins in healthcare settings across the country [ 4 , 20 ]. Our study emphasizes the importance and effectiveness of ASP initiatives in improving the indiscriminate prescription patterns of last resort antimicrobials used in the treatment of MDR organisms and potential survival benefits [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 Optimizing antibiotic use can play an important role in improving infection cure rates, preventing sepsis, reducing the unintended negative consequences of antibiotic use and possibly reducing costs. 12 The Antibiotic Stewardship in Hemodialysis (ASHD) White Paper Writing Group is a collaboration between CDC and the American Society of Nephrology (ASN). Given nationwide interest in optimizing antibiotic use in various patient populations, the objectives of the workgroup were to summarize current literature on antibiotic use in the outpatient hemodialysis setting and highlight strategies to improve antibiotic prescribing in hemodialysis.…”
Section: Purpose Focus and Scopementioning
confidence: 99%
“… 11 Optimizing antibiotic use can play an important role in improving infection cure rates, preventing sepsis, reducing the unintended negative consequences of antibiotic use and possibly reducing costs. 12 …”
Section: Purpose Focus and Scopementioning
confidence: 99%
See 2 more Smart Citations